2022
DOI: 10.3389/fnagi.2022.977321
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the parallel mediation influence of body mass index and depression on physical activity and cognitive function among 3,611 Chinese older adults

Abstract: BackgroundEngagement in physically active lifestyles brings multidimensional health benefits including better cognitive function. While prior studies examined the link between physical activity and cognitive function, a remaining unanswered question is what modifiable factors channel such effects.ObjectiveThis study investigates the extent to which subject’s body mass index (BMI) and depression mediate the link between physical activity and cognitive function among older adults in China.MethodsThis study build… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 44 publications
(45 reference statements)
0
1
0
Order By: Relevance
“…The previous study found that late adulthood cognitive function could be activated via communications to examine the mental well-being channel [ 73 ]. The physical and communication behavioural modifications can lead to linked improvements in both mental and cognitive wellbeing for older adults [ 74 ]. The communications ecology model may be relevant to an age-friendly community [ 75 ].…”
Section: Resultsmentioning
confidence: 99%
“…The previous study found that late adulthood cognitive function could be activated via communications to examine the mental well-being channel [ 73 ]. The physical and communication behavioural modifications can lead to linked improvements in both mental and cognitive wellbeing for older adults [ 74 ]. The communications ecology model may be relevant to an age-friendly community [ 75 ].…”
Section: Resultsmentioning
confidence: 99%